Profiling of three H3F3A-mutated and denosumab-treated giant cell tumors of bone points to diverging pathways during progression and malignant transformation - Hasenfratz, Marc; Mellert, Kevin; Marienfeld, Ralf; von Baer, Alexandra; Schultheiß, Markus; Roitman, P. D.; Aponte-Tinao, L. A.; Lehner, Burkhard; Moeller, Peter; Mechtersheimer, Gunhild; Barth, Thomas F. E. (Scientific reports, 2021)
Giant cell tumor of bone (GCTB) is a locally aggressive lesion of intermediate malignancy. Malignant transformation of GCTB is a rare event. In 2013, the humanized monoclonal antibody against receptor activator of nuclear factor-kappa b-Ligand (RANKL) denosumab was approved for treatment of advanced GCTB. Since then, several reports have questioned the role of denosumab during occasional malignant transformation of GCTB. We report on three patients with H3F3A-mutated GCTBs, treated with denosumab. The tissue samples were analysed by histomorphology, immunohistochemistry, and in two instances by next generation panel sequencing of samples before and after treatment. One patient had a mutation of ARID2 in the recurrence of the GCTB under treatment with denosumab. One patient developed a pleomorphic sarcoma and one an osteoblastic osteosarcoma during treatment. Sequencing revealed a persisting H3F3A mutation in the osteosarcoma while the pleomorphic sarcoma lost the H3F3A mutation; however, a FGFR1 mutation, both in the recurrence and in the pleomorphic sarcoma persisted. In addition, the pleomorphic sarcoma showed an AKT2 and a NRAS mutation. These data are inconclusive concerning the role denosumab plays in the event of malignant progression/transformation of GCTB and point to diverging pathways of tumor progression of GCTB associated with this treatment.